The effect of color as an element of theatrical decor on the recipient with Down syndrome - Assist.Prof. Dr. Mona Ahmed Hussein Hassan (Journal of Architecture, Art & Humanistic Science, 2024)
All studies have proven that art has a strong effect in treatment, and because theater is the father of arts, it must have an influential role on people with special needs, and the World Health Organization and then the state recommended attention to (disabled people), and the name of the Mongolians was changed to Down syndrome, attributed to the British doctor John This syndrome was first described by Jon Langhdown in 1862. In view of the large increase in their numbers, and in view of the community and families’ awareness of these cases, and after many experiments have proven that caring for those who are different, not the backward, society has gained useful individuals. Many of them are no longer dependent on society, but have become productive people. Some of them have professional handicrafts, including the actor, singer and broadcaster. Therefore, the state agencies, upon the recommendation of the President and UNESCO, sought to work on integrating the people of determination and the healthy, and all state agencies directed awareness campaigns about the nature and specifications of people with the syndrome. Down that they are different individuals in society, but they may be distinguished by caring for them and integrating them into society by turning them into useful elements. And discovering the characteristics and talents of a child with Down syndrome facilitates the process of communicating with him and integrating him with others of his peers while developing his abilities and capabilities. Hence, the researcher was interested in studying the effect of theater in general and color in theatrical decoration in particular on the skills of people with Down syndrome. Can theater art in general and color theater decoration in particular affect the recipient of Down syndrome? And how to benefit from theatrical decoration, which is an element of theatrical performance, and the researcher has assumedThe color in theatrical decoration has an impact on recipients with Down syndrome. The research aims to study the effect of color on theatrical decoration as one of the elements of theatrical performance and to contribute to the state's plan and community service to integrate people with Down syndrome. The researcher found that people with Down syndrome often have the ability to express themselves either in a limited way or in a way that is misunderstood by others. And that the experiments presented by the researcher in other fields were aimed at providing the recipient with Down syndrome with individual skills that may be life or educational, and that color was one of the most important elements or means that researchers resorted to to develop their awareness. They may be influenced by color as an element of theatrical decor.